2008
DOI: 10.1111/j.1600-0625.2008.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of the human bulge region: the quest to define useful in situ markers for human epithelial hair follicle stem cells and their niche

Abstract: Since the discovery of epithelial hair follicle stem cells (eHFSCs) in the bulge of human hair follicles (HFs) an important quest has started: to define useful markers. In the current study, we contribute to this by critically evaluating corresponding published immunoreactivity (IR) patterns, and by attempting to identify markers for the in situ identification of human eHFSCs and their niche. For this, human scalp skin cryosections of at least five different individuals were examined, employing standard immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
225
4
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(246 citation statements)
references
References 108 publications
(145 reference statements)
13
225
4
4
Order By: Relevance
“…Although both K15 and CD200 were expressed in the bulge, as expected, 9,11,23 our results revealed that the areas of expression for the two markers are distinct from each other. CD200 was expressed in a limited range around the bulge, whereas K15 was expressed widely in both the peri-bulge and sub-bulge areas (Figure 2a and b).…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271supporting
confidence: 82%
See 2 more Smart Citations
“…Although both K15 and CD200 were expressed in the bulge, as expected, 9,11,23 our results revealed that the areas of expression for the two markers are distinct from each other. CD200 was expressed in a limited range around the bulge, whereas K15 was expressed widely in both the peri-bulge and sub-bulge areas (Figure 2a and b).…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271supporting
confidence: 82%
“…As reported previously, 9,11,17,19,23 K15 (bulge marker), CD200 (bulge marker), CD34, and CD271 were strongly and differentially expressed in the outermost layer of the ORS in cells that adhered to the basement membrane ('basal cells'; Figure 1a). Other cytokeratins (K1 and K14) and integrins Figure 1 Biomarker expression profiles in human epidermis and the anagen hair follicle.…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271supporting
confidence: 77%
See 1 more Smart Citation
“…The sections were counterstained with Mayer's hematoxylin, washed with tap water, dehydrated, cleared and mounted in PERTEX (mounting medium for light microscopy, Histolab, Gothenburg, Sweden). Initially, reproduction of published immunoreactivity patterns for CK15 was used as an internal positive control as recommended by Kloepper et al (2008). Thereafter, sections from a case of melanoma and human squamous cervical carcinoma were used as positive controls for S100 and CK15 immunohistochemistry, respectively.…”
Section: Light Microscopy and Immunohistochemistrymentioning
confidence: 99%
“…These multipotent stem cells, called epithelial hair follicle stem cells (eHFSCs), are located in the bulge region -specifically, at the insertion site of the arrector pili muscle in the outermost layer of the outer root sheath [14,15] -and contribute to repopulation of the epidermis after injury. According to the results published by Abbas et al (2009Abbas et al ( , 2011, Kloepper et al (2008), and Sabeti et al (2013) [16,17,18,19] cytokeratin 15 (CK15), a stem cell marker, labels the cells in the bulge region of the human hair follicle, the outermost layer of the outer root sheath, the basal layer of the epidermis and eccrine glands, whereas other researchers found that the basal layer of normal epidermis is usually negative for CK15, and the bulge stem cells do not contribute to the interfollicular epidermis reconstitution [20]. A further controversy is added by Cotsarelis' publication reporting about the migration of the bulge cells to the interfollicular epidermis [21].…”
Section: Introductionmentioning
confidence: 99%